Low self esteem and its relation with psychological distress among dental students - Al-Ani, Ali Sabri Radeef; Faisal, Ghasak Ghazi (European Journal of Medical and Health Sciences (EJERS), 2019)
Since self-esteem has been recognized to predict health and psychological well-being, it is crucial to assess the self-esteem and its relation with psychological distress. Methodology: This study was conducted among 257 dental students. The psychological distress was assessed using the 12-item General Health Questionnaire (GHQ-12) while self-esteem was assessed using the adult form of the Coopersmith Self-Esteem Inventory. Results: Female students had significantly lower self-esteem compared to male students (51.4 and 59.1 respectively). There is a strong negative correlation between psychological distress and self-esteem (r= -0.5, p<0.00). Students with psychological distress had significantly lower mean self-esteem score compared to those who are not distressed (43.07 and 60.03 respectively). Conclusion: Low self-esteem is higher among female students and self-esteem is negatively correlated to psychological distress among undergraduate students.